Protective effect of silencing lncRNA HCP5 against brain injury after intracerebral hemorrhage by targeting miR-195-5p - Zhanhua Lu; Kun Huang (BMC Neuroscience)
Abstract Background Intracerebral hemorrhage (ICH) is a common subtype of stroke, characterized by a high mortality rate and a tendency to cause neurological damage. This study aims to investigate the role and mechanisms of lncRNA HCP5 in ICH. Methods We simulated ICH in vivo by injecting collagenase into rats and established an in vitro model using hemoglobin-treated BV2 cells. HCP5 and miR-195-5p levels were quantified by RT-qPCR. mNSS score was used to evaluate neurological deficits in the rats. The dry-wet weight method assessed the degree of brain edema. Cell viability and apoptosis rates were determined using the CCK-8 assay and flow cytometry, respectively. The targeting relationship between HCP5 and miR-195-5p was confirmed using dual-luciferase reporter assays and RNA immunoprecipitation. ELISA was utilized to measure inflammatory factors, and commercial kits were used to detect MDA and ROS levels. Results In the ICH model rats, HCP5 levels were significantly elevated. It was also found that silencing HCP5 significantly alleviated brain edema and neurological deficits in the ICH rats, and there was a marked improvement in ICH-induced neuroinflammation and oxidative stress. Moreover, HCP5 was found to sponge miR-195-5p, and inhibiting miR-195-5p could counteract the neuroprotective effects of silencing HCP5. Similar results were obtained in the in vitro experiments with BV2 cells. Conclusions Silencing HCP5 can alleviate brain edema, neurological dysfunction, neuroinflammation, and oxidative stress caused by ICH via miR-195-5p.